(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article discusses the definition of the category of «innovation» in the cultural and artistic aspects. The aim of the study is to identify the specific features of innovations in culture, art and choreography in particular. This will allow introducing the term «innovation» into Kazakh ballet studies, as well as specifying the properties (meaning, scope, limits) of this phenomenon in a theoretical aspect. Applying comparative analysis and scientific generalization as the main research methods, the author studied the modern culturological theories of innovations and singled out characteristics in their main points that can be found in choreography. The author described the main features of the term innovation in dance, highlighted the semiotic aspects of the concept, which are reflected in the practice of choreography. This will provide an opportunity to proceed to the next stage of the study – the study of directorial innovations in choreography from philosophical, cultural and artistic points of view. Key words: innovation, culture, art, theater, choreography.